Increased Of VVPR Through Quantum Teaching Model With Student Worksheet Based On Multiple Representation - Nila Karmila; I Ketut Mahardika; Agus Abdul Gani (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
This research is classroom action research. The purpose of this research is to describe verbal and visual physics representation (VVPR) students after using quantum teaching model with student worksheet based on multiple representations on physics learning in class XI Science 1 SMAN 1 Pakusari. The design of this research is using Hopkins cycle. Methods of data collection in this research are interviews, observation, documentation, and test. Data obtained from this research are the verbal representation and visual representation. Data analysis technique is used descriptive analysis techniques. Increasing the capability of representation from each cycle using the formula normalised gain. The results of this research from the N-gain value on pre cycle to cycle III for verbal representation is 0.82 in high category and visual representation is 0,82 in the high category. The conclusion of this research is there is an increase of verbal representation and visual representation ability students after using Quantum Teaching model with student worksheet based on multiple representations on physics learning in class XI Science 1 SMAN 1 Pakusari